Improvement scheme of OSS intelligence capability for autonomous network - ZHAO Yongjian; ZHAO Zhanchun; ZHANG Ding; LI Shanshan; LIU Zhifei (Dianxin kexue)
Driven by both business and technology, the communication industry is focused on smart network operations. It is an industry consensus to promote network intelligent operation with autonomous networks as the driving force. It was analyzed that operational support system (OSS) was the core component of the three-layer architecture of autonomous network, and the key to improve the level of autonomous networks was to enhance the intelligence capability of OSS. Specific implementation schemes such as the definition method of OSS product business scope, the analysis of the shortcoming of OSS product ability,and systematic improvement of OSS product capabilities driven by autonomous networks were elaborated. The solution was described in detail using the digital operation value scenario of broadband services as an example. Finally, the intelligent ability map of OSS driven by autonomous network was discussed. Improving the intelligence capability of OSS for autonomous network can effectively promote the research and development direction of OSS, and guide the planning and research and development of OSS products for operators.